2022
DOI: 10.1007/s11259-022-09910-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of avian rotavirus infections in broiler chicks from commercial flocks with different performance efficiency indexes

Abstract: The aim of this study was to investigate and compare the frequency of occurrence of avian rotavirus (AvRV) in poultry flocks according to its Performance Efficiency Index (PEI) scores. A total of 256 individual intestinal content samples of small sized-chicks (runts) with clinical signs of Runting Stunting Syndrome (RSS) and 24 clinically healthy chicks (control) were collected from twelve flocks in southern Brazil with different PEI scores: good ( n = 4, PEI mean = 365); moderate ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…RVD first detected as virus 132 and rotavirus-like viruses (McNulty et al 1981) has been reported from many places, including a report from Nigeria (Pauly et al 2017). RVD was identified as one of the causes in the pathogenesis of runting and stunting syndrome having a high negative impact on the poultry sector (Otto et al 2006, Gallego et al 2022. Recently, rotavirus has been found to be the single causative agent of young pigeon disease syndrome with high mortality (Harzer et al 2021).…”
mentioning
confidence: 99%
“…RVD first detected as virus 132 and rotavirus-like viruses (McNulty et al 1981) has been reported from many places, including a report from Nigeria (Pauly et al 2017). RVD was identified as one of the causes in the pathogenesis of runting and stunting syndrome having a high negative impact on the poultry sector (Otto et al 2006, Gallego et al 2022. Recently, rotavirus has been found to be the single causative agent of young pigeon disease syndrome with high mortality (Harzer et al 2021).…”
mentioning
confidence: 99%